Sensor Technology for Sports Monitoring - Linnamo, Vesa (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In order to be able to analyze and give proper advice on sport techniques, it is important to understand the biomechanical and physiological demands of different sports. In a coaching situation, feedback to the athlete should be given without too much delay. Over the past decades, sensor technology-related to sports monitoring has developed with huge steps. Senors are lighter, data transmission is mostly wireless, and software applications are more user-friendly. This reprint is addressed to all kinds of sensors that are currently being used for monitoring different sports.